Design of a Web-Based OSIS E-Voting System Using the Waterfall Method at SMPN 3 Naringgul - Aziz Stiawan Amrullah; Tedjo Darmanto; Moch Irwan Hermanto (Universitas Suryakancana Cianjur, 2025)
Background: The election of the Student Council President (Ketua OSIS) at SMPN 3 Naringgul has so far been conducted manually, which often causes errors in vote counting and delays in announcing results. Objective: This study aims to develop a web-based E-Voting System to improve the efficiency, accuracy, and transparency of OSIS elections. Method: This research used a structured Waterfall Methodology for software development, covering requirement analysis, system design with UML diagrams, implementation using PHP/MySQL, and system testing using Black-Box Testing for verification. Results: The resulting e-voting system has features such as secure voter login, a candidate selection interface, real-time vote counting, and an admin panel for data management. Testing results show that the system can speed up the election process, minimize human error, and increase result transparency. Conclusion: The developed system effectively supports the digitalization of school election management and provides a faster and more reliable alternative compared to manual election methods.